Characterization and transport properties of pva–libob based polymer electrolytes with application in dye sensitized solar cells / Ikhwan Syafiq Mohd Noor - Ikhwan Syafiq , Mohd Noor (2016)
The objectives of this work are to (i) produce high conducting solid and gel poly(vinyl alcohol) (PVA) based polymer electrolytes incorporated with lithium bis(oxalato)borate (LiBOB) salt, (ii) determine and analyse the transport properties of charge carriers of solid and gel PVA–based electrolyte and (iii) study the influence of LiBOB–TBAI and LiBOB–TBAI–BMII gel electrolyte on the performance of dye sensitized solar cells (DSSCs). Three electrolyte systems were prepared i.e. PVA–LiBOB solid and gel electrolytes, PVA–LiBOB–TBAI–I2–DMF and PVA–LiBOB–TBAI–BMII–I2–DMF gel electrolytes. The highest room temperature conductivity (σ) obtained for PVA– LiBOB solid electrolyte was 2.83×10-4 S cm-1 with 60 wt.% PVA: 40 wt.% LiBOB. Mobility (μ) and number density (n) was 9.58×10-7 cm2 V-1 s-1 and 1.85×1021 cm-3, respectively. In gel form the σ of this electrolyte with 60 wt.% PVA–40 wt.% LiBOB (B0 electrolyte) is enhanced to 7.31×10-3 S cm-1. μ and n was 8.41×10-5 cm2 V-1 s-1 and 5.42×1020 cm-3, respectively. In order to use these electrolytes in DSSC, tetrabutylammonium iodide (TBAI) and iodine (I2) have been added in B0 electrolyte to generate redox process. The electrolyte with composition 17.53 wt.% PVA–1.75 wt.% LiBOB–9.93 wt.% TBAI–0.68 wt.% I2–70.11 wt.% DMF (B5 electrolyte) exhibits σ of 5.13×10-3 S cm-1 and the DSSC utilizing this electrolyte exhibits the highest efficiency of 6.11%. The values of μ and n obtained were 9.58×10-5 cm2 V-1 s-1 and 3.35×1020 cm-3, respectively. In a further attempt to increase solar efficiency, 1–butyl–3– methylimidazolium iodide (BMII) was added to B5 electrolyte and efficiency becomes 7.28% when added with 9 wt.% BMII. The conductivity is enhanced to 7.52×10-3 S cm-1 and μ is 9.52×10-5 cm2 V-1 s-1 and n is 4.93×1020 cm-3. Conductivity for all electrolytes prepared in this work increased with increasing temperature. This work also reports the significance of Li+ in determining how the performance of the DSSC can be controlled.